Penerapan Wireless Sensor Network Dan Realtime Operating Sistem Pada Otomasi Pelayanan Restoran - Hamzul Azkia (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The restaurant is a building that is organized and run commercially, in every restaurant that provides good service to its guests. This research method combines the concept of WSN and Real Time Operating System (RTOS), where RTOS will later improve WSN performance in carrying out tasks on the system. The result of this research is the realization of the prototype by integrating the WSN system (3 units each of 4 ultrasonic sensors), The results of the accuracy and precision analysis of the prototype are obtained with a sensor detection distance of 30cm with a standard deviation of 1.009978 and the average delivery time from WSN to the server is 0, 53 seconds . The performance of the WSN system with this RTOS by experimenting with the initial state of 2 units, then reducing it to 1 unit gets the same delivery time as testing 2 units, while when it is added to 3 units there is an increase in delivery time of 3.125%. So it can be said that the performance of the system uses 3 units which takes longer.